Toxicity study of the ethanolic extract of Moringa concanensis Nimmo leaves in wistar rats - BRINDHA BANU BALAKRISHNAN; KALAIVANI KRISHNASAMY (International Journal of Pharma and Bio Sciences, 2018)
Moringa concanensis Nimmo plant leaves are widely used in traditional medicine throughout India for the treatment of various ailments including menstrual pain, high blood pressure, jaundice, constipation, skin tumour, cholesterol, and diabetes. There is no literature survey of the toxicity evaluation of the ethanolic extract of Moringa concanensis Nimmo leaves.Therefore, the objective of this study was to evaluate the potential toxicity and to check the safety of ethanolic extract M. concanensis Nimmo, through the method of acute oral administration in Wistar rats. During the experimental period, male Wistar rats were orally treated with the ethanolic extract of M. concanensis Nimmo at the doses of 100, 250, 500, 1000 and 2000 mg/kgand observed thereafter, for a total of 14 days. Every day the general behavior of the rats was noted during the experimental period. Body weight, haematological analysis and histopathological examination were carried out at the end of the experiment period. During the acute toxicity study, no sign of mortality was observed when rats were administered dose of 100, 250, 500, 1000 and 2000 mg/kg (P<0.05). Similarly, there were no significant changes in body weight, food consumption, hematology, gross necropsy and histopathological examinations. The results of the current study explored that the treatment with this plant extract for 14 days did not produce significant toxicity. Therefore, our study suggests that the use of appropriate level of M. concanensis Nimmo extract as traditional medicine should have a wide range of safety for its therapeutic use.